Acute Time-Course Changes in CCL11, CCL2, and IL-10 Levels After Controlled Subconcussive Head Impacts: A Pilot Randomized Clinical Trial. Issue 5 (September 2020) - Huibregtse, Megan E.; Ejima, Keisuke; Chen, Zhongxue; Kalbfell, Rachel M.; Koppineni, Alekhya; Kawata, Keisuke
Abstract : Objective: To examine changes in plasma levels of CCL11, CCL2, and IL-10 after 10 controlled soccer headers. Setting: Laboratory setting. Participants: Thirty-nine healthy soccer players with at least 3 years of soccer heading experience, between 18 and 26 years old, and enrolled at a large public university. Design: In this randomized clinical trial using a soccer heading model, participants were randomized into the heading ( n = 22) or kicking-control ( n = 17) groups to perform 10 headers or kicks. Main Measures: Plasma levels of CCL11, CCL2, and IL-10 at preintervention and 0, 2, and 24 hours postintervention. Results: Mixed-effects regression models did not reveal any significant group differences in changes of plasma CCL11, CCL2, or IL-10 levels from preintervention. Within the heading group, there was a statistically significant time by years of heading experience interaction with 2.0-pg/mL increase in plasma CCL11 each year of prior experience at 24 hours postintervention ( P = .001). Conclusion: Findings from this study suggest that 10 soccer headers do not provoke an acute inflammatory response. However, the acute CCL11 response may be influenced by prior exposure to soccer headers, providing a precedent for future field studies that prospectively track head impact exposure and changes in CCL11. Abstract : Supplemental Digital Content is Available in the Text.